Numerical simulation and optimization on the thermofluidic behavior of thermal management system in hydrogen fuel cell - Jia-Hao Li; Yu Chen; Jia-Bao Wang; Ji-Qiang Li; Heng Xu; Ji-Chao Li; Jeong-Tae Kwon (Results in Engineering, 2024)
Hydrogen can serve as an abundant, green, low-carbon, and widely applicable secondary energy source, holding significant importance in building a clean, low-carbon, secure, and efficient energy system and achieving carbon peak and carbon neutrality goals. In the research of hydrogen fuel cells, thermal management, particularly cooling methods, plays a crucial role in the operation of the battery units. This paper primarily focuses on cooling methods in thermal management, using factors such as arrangement, cooling medium, and environmental temperature as variables to establish a simulation model for the thermal behavior of cylindrical hydrogen fuel cells and conduct a parametric study. The research findings indicate that enveloping the battery with a cooling medium can enhance heat dissipation by 19 %. Arranging the hydrogen fuel cell units in a symmetrical rectangular pattern yields excellent heat dissipation results. The battery's maximum temperature increases with the rise in environmental temperature, with every 5 K increase in environmental temperature resulting in a 1.01 % rise in the battery's maximum temperature.